"HugMe" development of an inclusive toy: first insights - Ferreira, Rosaria (2016)
In childhood, play is critical to the successful development of children and it can be regarded as the most important activity in their daily life, allowing interaction and discovery of the world around them. As a consequence, it is important to ensure that this birthright is protected and accessible to every child, including those with special needs. Professionals, such as therapists, are often in a position where they can take advantage of the inclusion of toy in their therapies with children, with habilitation and rehabilitation in mind. Although, toys are not all alike and they must be carefully thought in order to be able to fulfill the child's needs. This paper presents a proposal for an inclusive toy, entitled "HugMe", especially designed for children with special needs, but that could be also used by other general developing children.